Late Permian High-Ti Basalt in Western Guangxi, SW China and Its Link With the Emeishan Large Igneous Province: Geochronological and Geochemical Perspectives - Zhang, Chenguang; Zeng, Renyu; Li, Changming; Jiang, Jian; Wang, Tianguo; Shi, Xingjun (Frontiers in Earth Science, 2021)
To investigate any genetic link between the high-Ti basalt in western Guangxi and Late Permian Emeishan flood basalt, we performed whole-rock geochemical and Sr-Nd isotope and zircon U-Pb-Hf isotope analyses on the basalts from the Longlin. The results indicate that the Longlin basalt in the Tongdeng area has relatively high SiO2and low MgO and TFe2O3 contents. The rocks have zircon εHf(t) = -0.42–6.41, whole-rock (87Sr/86Sr)i = 0.707167–0.707345, and εNd(t) = -2.5 to -2.14. In contrast, the Longlin basalt in the Zhoudong area has relatively low SiO2 and high MgO and TFe2O3 contents. The rocks have whole-rock (87Sr/86Sr)i = 0.706181–0.706191 and εNd(t) = -0.57 to 0.69. All the Longlin basalt samples display LREE enrichments and HREE depletions, and with indistinct δEu and δCe anomalies. LA-ICP-MS zircon U-Pb dating on three Longlin basalt samples (from different localities) yielded consistent weighted average age of 257.9 ± 2.6 Ma (MSWD = 0.55), 259.5 ± 0.75 Ma (MSWD = 3.0) and 256.7 ± 2.0 Ma (MSWD = 0.68), indicating a Late Permian emplacement age coeval to the Emeishan flood basalts. Geochemical features show that the Longlin basalt was formed from ~1.0 to 2.0 % partial melting of the lithospheric mantle in the spinel–garnet transition zone. The primitive magma may have experienced mafic mineral fractionation and varying degrees of crustal assimilation. Considering the similar geochemical and geochronological features between the Longlin basalt and Emeishan flood basalts, we interpreted that the former was formed in an intraplate rift setting, probably associated with the Emeishan mantle plume. The high-Ti features may have linked to the relatively low degree of partial melting in the deep lithospheric mantle.